Afghanistan Unlocking the Potential of Horticulture : Discussion Note and Input to Agribusiness Jobs Charter - World Bank (World Bank, Washington, DC, 2017)
Afghanistan possesses a rich horticultural history, with a number of unique products, such as dried fruit, that are still renowned in various parts of the world. The period of conflict that has plagued Afghanistan for the past 40 years has, however, severely disrupted supply chains and markets for horticultural products and, in particular, hindered the ability of traders and producers to export products to high-value markets. The following sections provide an overview of the horticultural sector in Afghanistan and its various components. Section 1.1 describes the history and economic importance of horticulture in Afghanistan; section 1.2 describes the endowments and infrastructure that support the production and trade of horticultural crops in Afghanistan; section 1.3 presents an overview of the nature of horticultural inputs in Afghanistan and details methods for producing horticultural crops; section 1.4 describes the structure of post-harvest activities; section 1.5 reviews the processing and marketing of horticultural products in Afghanistan; section 1.6 presents and overview of the recent performance of the horticulture sector in Afghanistan; and section 1.7 describes recent and current policies and programs focusing on the horticulture sector in Afghanistan. The report is organized as follows: chapter one summarizes the recent literature on the horticulture sector; chapter two presents the results of the Survey undertaken for this report; and chapter three lists recommendations and next steps.